Paradigm shift in the pharmacological treatment of type 2 diabetes mellitus - Tejal Lathia (Wolters Kluwer Medknow Publications, 2020)
The options for pharmacological management of type 2 diabetes mellitus have exploded over the last decade or so. Availability of a variety of new drugs, oral as well as injectable, has made the choice of treatment more complex and challenging. Over a decade or so ago, glycemic (glucometabolic) control was the main target of treatment in patients with type 2 diabetes mellitus - usually with metformin, sulfonylureas (SU), thiazolidinediones, and insulin (the traditional quartet). There is conflicting evidence on the cardiovascular (CV) effects of the traditional quartet of drugs. The almost serendipitous benefit of sodium-glucose transporter 2 (SGLT2) inhibitors on CVD and kidney disease in patients with type 2 diabetes mellitus has revolutionized the way we view the treatment of diabetes. . What the physician needs to remember when prescribing this drug is - right patient and right intent.